PENGEMBANGAN PEMBELAJARAN IPA BERBASIS KEARIFAN LOKAL (HAMIS BATAR) UNTUK MENINGKATKAN LITERASI SAINS SISWA (STUDI LITERATUR) - Tabun, Yohana Febriana (Jurnal Pendidikan Dasar Flobamorata, 2024)
The urgency of this study is that the learning model is in accordance with the 2013 curriculum consisting of several learning models namely guided inquiry,problem based learning, etc. Each learning model provides a learning effect and a driving effect. The learning effect is related to learning outcomes while the driving effect is related to the character values ​​that emerge after the learning process. Local cultural wisdom is very appropriate for building student character values ​​which are an accompanying effect in a learning process at school. Therefore, this study aims to examine scientific articles that discuss learning based on local wisdom so as to answer the intended learning and herding effects. Another expected result of developing this learning model is that it can improve scientific literacy skills.